2013
DOI: 10.5812/jjm.8333
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Survey on Leptospiral Infection Among Wild Rats (Rattus rattus) of Ahvaz District, Southwest of Iran: A Preliminary Study

Abstract: Background:Leptospirosis is an important zoonotic disease caused by pathogenic Leptospira which can infect both humans and animals. This disease is caused by various serovars of Leptospira interroganssensu lato infection. Rats are known to be one of the most important reservoirs and transmission sources of leptospirosis. However, the status of leptospirosis in wild rats has been unknown in many areas of Iran. Objectives: This study was conducted to evaluate the seroprevalence of leptospiral infection in wild r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
(8 reference statements)
1
6
1
Order By: Relevance
“…Considering the similar ecological conditions found outside the District of Gampaha, we assume that this observation is also true outside the division. Our finding is consistent with several other reports that rodents present a reservoir host in most parts of the world [9, 11, 15, 19, 20]. …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Considering the similar ecological conditions found outside the District of Gampaha, we assume that this observation is also true outside the division. Our finding is consistent with several other reports that rodents present a reservoir host in most parts of the world [9, 11, 15, 19, 20]. …”
Section: Resultssupporting
confidence: 94%
“…Rats are notorious reservoir hosts of leptospires but domestic and wild animals may be transient or persistent shedders of leptospires [9–11]. Unfortunately, people living in Sri Lanka have a poor level of knowledge around potential risk factors for leptospirosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…From the total 17 Leptospira positive rats, a greater number of female (64.7%) and adult (70.6%) rats were detected. This is contrary with the finding by Mosallanejad et al [ 23 ] who studied the seroprevalence of Leptospira in 120 wild rats in Iran. They reported that positive Leptospira was found in 2.5% male and 0.83% female rats.…”
Section: Discussioncontrasting
confidence: 90%
“…The finding from previous researcher indicated that higher prevalence of Leptospira was detected in other animals such as cattle (53.8%), horse (27.9%), buffalo (58.7%), and donkey (40.0%) than in rats (3.3%) in Ahvaz, Iran. This is because those animals which live in groups near water may have additional access to the contaminated environment and stagnant water than rats [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are important reservoir hosts or carrier animals and their infection may be associated with varying degrees of renal disease (Dirsmith et al, 2013). Since leptospira have been detected in some species of squirrel (Montes Aliaga et al, 2011;Dirsmith et al, 2013;Gozzi et al, 2013;Mosallanejad et al, 2016), human transmission is therefore plausible being a zoonotic disease and also considering human-animal interaction. Very few data exist in the literature as regards the role of squirrels in the epidemiology of leptospirosis (Cilia et al, 2021) especially in developing countries like Nigeria (Ajayi et al, 2017) while very little or no information exists about the knowledge of squirrels as carrier animals for leptospirosis within the University of Ibadan.…”
Section: Introductionmentioning
confidence: 99%